Unrealized potential and residual consequences of electronic prescribing on pharmacy workflow in the outpatient pharmacy. (23rd October 2013) - Nanji, Karen C; Rothschild, Jeffrey M; Boehne, Jennifer J; Keohane, Carol A; Ash, Joan S; Poon, Eric G
Abstract: Introduction Electronic prescribing systems have often been promoted as a tool for reducing medication errors and adverse drug events. Recent evidence has revealed that adoption of electronic prescribing systems can lead to unintended consequences such as the introduction of new errors. The purpose of this study is to identify and characterize the unrealized potential and residual consequences of electronic prescribing on pharmacy workflow in an outpatient pharmacy. Methods A multidisciplinary team conducted direct observations of workflow in an independent pharmacy and semi-structured interviews with pharmacy staff members about their perceptions of the unrealized potential and residual consequences of electronic prescribing systems. We used qualitative methods to iteratively analyze text data using a grounded theory approach, and derive a list of major themes and subthemes related to the unrealized potential and residual consequences of electronic prescribing. Results We identified the following five themes: Communication, workflow disruption, cost, technology, and opportunity for new errors. These contained 26 unique subthemes representing different facets of our observations and the pharmacy staff's perceptions of the unrealized potential and residual consequences of electronic prescribing. Discussion We offer targeted solutions to improve electronic prescribing systems by addressing the unrealized potential and residual consequences that we identified. These recommendations may be applied not only to improve staff perceptions of electronic prescribing systems but also to improve the design and/or selection of these systems in order to optimize communication and workflow within pharmacies while minimizing both cost and the potential for the introduction of new errors.